Assessment and fishery of shellfish stocks in the Barents and White Seas in 2000–2020 - Bakanev, S. V.; Matyshkin, V. B.; Sennikov, A. M.; Stesko, A. V. (Vestnik MGTU, 2022)
Hydrobionts have a high nutritional value and are the most important component of the food supply for the population of Russia. In the course of the study, the characteristics of the stocks and fisheries of the king crab, opilio snow crab, northern shrimp, Icelandic scallop, sea green urchin and other commercial invertebrates in 2000–2020 are presented. The raw material base of the fishery of the king crab and snow crab is used in full; the indices of their commercial biomass are 215 and 430 thousand tons, respectively; development of TAC – more than 90 %. While maintaining the current management strategy, their commercial stocks will be at a stable level or increase. The commercial stock of the northern shrimp in the Barents Sea and adjacent waters is in a satisfactory condition (at the end of 2020 it was estimated at 2.2 million tons); the distribution density of shrimp in the Russian EEZ has halved. The resource base of the Icelandic scallop fishery in the Barents Sea is not exploited due to the depressive state of the stock: the median of commercial biomass is at the level of 200 thousand tons, which is below the boundary biomass target (224 thousand tons). The growth in the catch of the sea urchin is due to the increased interest of fishers in this object. The annual catch of the sea urchin does not exceed 10 % of the recommended one, fishing efforts are unevenly distributed over different parts of the Murman coast. Cucumaria, mussel, trumpeter, shrimp bear cub, clema, euphausiids are caught in small quantities and remain in the category of underutilized fishery objects. Гидробионты обладают высокой пищевой ценностью и являются важнейшим компонентом продовольственного обеспечения населения России. В ходе исследования представлена характеристика запасов и промысла камчатского краба, краба-стригуна опилио, северной креветки, исландского гребешка, морского зеленого ежа и других промысловых беспозвоночных в 2000–2020 гг. Сырьевая база промысла камчатского краба и краба-стригуна используется в полном объеме; ...